(untitled) (LACCEI, 2024)
Floods are one of the costliest natural disasters in the world and represent a common hazard to the Caribbean, specifically to Puerto Rico. Floods can be local, impacting neighborhoods and communities, or large-scale, impacting regions or the entire Island. Some floods develop slowly, sometimes over a day or more. However, flash floods can develop quickly, sometimes in just a few minutes and without visible rain signs. Urban development still needs to integrate water systems safely and sustainably into urban space. This article explains an alternative concrete design could reduce flood areas and address this to manage urban flood risks better. Pervious concrete constitutes an efficient best management practice stormwater management solution not just for flood mitigation, but also for water reuse.